Guided K-best Selection for Semantic Parsing Annotation - Belyy, Anton; Huang, Chieh-yang; Andreas, Jacob; Platanios, Emmanouil Antonios; Thomson, Sam; Shin, Richard; Roy, Subhro; Nisnevich, Alex; Chen, Charles; Van Durme, Ben (ACL 2022, 2022)
Collecting data for conversational semantic parsing is a time-consuming and demanding process. In this paper we consider, given an incomplete dataset with only a small amount of data, how to build an AI-powered human-in-the-loop process to enable efficient data collection. A guided K-best selection process is proposed, which (i) generates a set of possible valid candidates; (ii) allows users to quickly traverse the set and filter incorrect parses; and (iii) asks users to select the correct parse, with minimal modification when necessary. We investigate how to best support users in efficiently traversing the candidate set and locating the correct parse, in terms of speed and accuracy. In our user study, consisting of five annotators labeling 300 instances each, we find that combining keyword searching, where keywords can be used to query relevant candidates, and keyword suggestion, where representative keywords are automatically generated, enables fast and accurate annotation.